The Impact of Energy Consumption and Trade Openness on Economic Growth in Uzbekistan: A Vecm Approach - Halmuratov, Gofur; Madraximov, Qaxramon; Zakirova, Gulnoza; Xolmuratov, Xolilla; Djumabayeva, Shaira; Yaqubova, Yulduz; Xolmurotov, Fozil (International Journal of Energy Economics and Policy, 2025)
This study aims to study the long-term impact of energy consumption and trade openness on GDP per capita growth for the economy of Uzbekistan. The study was based on data from 1990 to 2023, and long-term relationships between variables were analyzed using VECM (Vector Error Correction Model). According to the results of the analysis, a 1 unit increase in energy consumption increased GDP per capita by 3.79 units, while a 1 unit increase in trade openness decreased GDP by 12 units. This situation shows that energy consumption is one of the main factors of the economic growth of Uzbekistan, but the negative impact of trade openness is mainly related to the high share of imports and low competitiveness of the national industry. According to the results of the analysis, to ensure the positive impact of trade openness on national economic growth, it is important to introduce policies aimed at developing national industry and improving energy efficiency. The research findings provide valuable recommendations for the effective use of energy resources for the country’s economy and the revision of foreign trade policies.